Evaluation of multivariate integrals via fluctuationlessness theorem and Taylor's remainder - (:unkn) unknown (My University, 2009)
A recently developed Fluctuationlessness Method is used in approximating the multiple remainder terms of the integral of the multivariate Taylor expansion. This provides us with a new numerical integration method for multivariate functions. © 2009 American Institute of Physics.
Keywords: Fluctuationlessness Theorem; Multivariate Approximation; Multivariate Taylor's Theorem; Numerical Integration